2020
DOI: 10.4102/aej.v8i1.415
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of eThekwini Municipality’s regeneration programmes on littering and dumping

Abstract: Background: South African cities have been beleaguered with urban deterioration challenges, especially dumping and littering, notwithstanding the regulatory framework and the continuous clean-up programmes undertaken by municipalities. This article identifies the challenges within eThekwini Metropolitan Municipality in addressing littering and dumping, and recommends improvements towards urban regeneration efforts.Objectives: To critically evaluate compliance of legislation and efficacy of the urban regenerati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…Both Govender and Reddy 42 and Salvia et al 43 confirm the constructions of similar value systems and personality traits of those who litter. [44][45][46] Chaudhary et al 6 identified five stages of litter research in developed countries.…”
Section: Theme 1: Value Systems and Personality Traitsmentioning
confidence: 76%
“…Both Govender and Reddy 42 and Salvia et al 43 confirm the constructions of similar value systems and personality traits of those who litter. [44][45][46] Chaudhary et al 6 identified five stages of litter research in developed countries.…”
Section: Theme 1: Value Systems and Personality Traitsmentioning
confidence: 76%
“…One of the major constraints highlighted by the street vendors in her study was the lack of infrastructure for proper waste management such as waste receptacles. Chitotombe's (2014) research in Harare, Zimbabwe, as well as studies by Govender and Reddy (2020) and Alfers et al (2016) in Durban, confirm the necessity to have sufficient and effective infrastructure for waste generated by the street vendors (such as food waste and the packaging in which the food is sold). The need for proper waste infrastructure is amplified by its effect on waste disposal behaviour.…”
Section: Theme 1: Reasons For Littering Theme 11: Street Vendors' Per...mentioning
confidence: 86%
“…As far as could be ascertained, literature focusing on littering and street vending does not frame the issues as wicked problems or utilise complexity theory as a lens. Solutions presented by different authors from developing countries, include public education, the need for new and updated service levels, improved infrastructure, increased monitoring and evaluation, effective leadership and participatory governance, increased citizen involvement, diminishing of negative behaviour patterns, effective compliance by the state (municipalities), increased effective enforcement of laws; effective waste management systems, policies to reduce urban poverty, and political will to mention but a few (Arias, 2019;Govender & Reddy, 2020;Mlambo, 2021;Nkwocha & Okeoma, 2009;Sinay, 2019). These studies propose the creation of bargaining and negotiating platforms to counter the lack of transparency and top down decision-making structures towards participatory governance structures and processes.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations